Reflections on Change in Arts-based Research: The experience of two music therapists - Seabrook, Deborah Melissa; Arnason, Carolyn (Voices: A World Forum for Music Therapy, 2010)
<!–[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Arial Unicode MS"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:none; mso-hyphenate:none; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Arial Unicode MS"; mso-font-kerning:.5pt; mso-ansi-language:EN-CA; mso-fareast-language:AR-SA; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; –> <!–[endif]–> The process of engaging in arts-based research is unique; it draws upon the creative essence of the researcher to work with artistic forms which carry intangible information that is perhaps unknowable by other means. In this process, the researcher is engaged wholly; all faculties of the person are drawn into the artistic world. This article explores the experiences of two music therapists conducting arts-based research studies, weaving together distinct narratives with common themes. The reader is taken along the journey of two separate music therapy research projects: one whose participants are a group of music therapists, one whose participant is a child living with mental health challenges. Thinking retrospectively, the researchers discuss links between their personal artistry and the arts-based research process, exploring issues such as trust, creativity, and the credibility of information carried in artistic media. Visual art, musical excerpts and creative writing are included. By exploring the professional and personal journeys as music therapists in the arts-based research process we highlight the strengths and challenges of this approach that shaped our studies and gave light to emergent understandings through the arts.